IMPLEMENTASI FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DALAM UPAYA MEMPERKUAT SISTEM PRESIDENSIAL DI INDONESIA - Putu Eva Ditayani Antari (Universitas Kristen Satya Wacana, 2020)
The House of Representatives of the Republic of Indonesia (DPR) has a supervisory function to the President's performance accompanied by the right to propose the dismissal of the President to the People’s Consultative Assembly of the Republic of Indonesia (MPR), as the implementation of the oversight function. However, in a presidential system, this is contrary to the terms of the fixed term executive. Also, the politicization of the DPR in the use of these rights raises the perception that the oversight function will weaken the presidential system. This is further researched and presented in descriptive-analytic writing, using normative legal research method. Based on the analysis, the DPR's supervisory function in the presidential system does not weaken the presidential system. Supervision is a balance and supervision of the power of the President. DPR as a supervisory institution shall obey the principles of transparency, accountability, independence, and impartiality. In addition, the existence of the Constitutional Court as a determinant of the validity of the proposal to dismiss the President also can prevent politicization in the dismissal of the President. Thus the DPR's supervisory function was created which was able to support the running of the presidential system and establish a balanced power between 3 (three) fields of state power according to Montesquieu's perspective.